Classification and categorization of the constrained environments in nuclear/radiological installations under decommissioning and dismantling processes - Aspe, Frederic; Idoeta, Raquel; Auge, Gregoire; Herranz, Margarita (Progress in nuclear energy (New series), 2020)
INSIDER is an EU Horizon 2020 research project, within the topic NFRP-7 of the EURATOM programme, that aims to develop and validate a new and improved integrated characterization methodology and strategy for the nuclear decommissioning and dismantling operations (D&D) of nuclear power plants, and post-accidental land remediation of nuclear facilities under constrained environments. In line with this general objective, the definition and implementation of the practical considerations surrounding the radiological characterization of nuclear/radioactive facilities subject to a D&D programme is under development. . In-situ measurements are key for this radiological characterization. However, in some cases these measurements have to be carried out under constrained conditions, which poses some challenges to their realization. A constrained environment is a general term that includes all types of environment that hinder the choice of a non-destructive in-situ measurement method. In the context of this paper, it is applied to different situations: radioactive levels of the area to be characterised, difficult accessibility of this area, type and properties of the materials contained in it, as well as the possible presence of other environmental hazards, such as asbestos, chemical and/or organic/biological ones. In this context, an analysis of the suitability of existing methodologies for in-situ measurements in constrained environment is being carried out. The first step to accomplish this task is to describe the constrained environments that could appear in the different nuclear/radioactive facilities and their respective challenges. This paper includes a description of the different constrained environments, showing their corresponding challenges and a classification of the constraints, and it provides a series of tables linking the installations and areas inside them with the different constraints that appear. In the case of the radioactive constraints, a description of the expected level of their impact depending on the different D&D steps also appears.